Dynamic Analysis of Major Components in the Different Developmental Stages of Tenebrio molitor - Yu, Xiao; He, Qiang; Wang, Dun (Frontiers in Nutrition, 2021)
The yellow mealworm, Tenebrio molitor is an important resource insect with high protein percentage and widely farmed in many countries. In this study, the content dynamic for protein, fat, chitin and other components in the whole life circle of yellow mealworms were analyzed by chemical analysis from different developmental stages and combining with their growth conditions. The results of components dynamic in different development stages showed that the percentage of protein, fat and chitin were the highest in the larval stage, pupal stage and adult stage, respectively. And the results of amino acid composition dynamic indicated comparatively higher essential amino acids in the earlier instar (eg. before 9th instar) larvae while the chitin and fat percentage were less than mature larvae. Therefore, the larvae in earlier instars were better than the final instar as the insect farming harvest time. And the larvae in earlier larval stage consumed dramatically less feed and could effectively reduce the farming cost for insect farmers. This finding provides an alternative option to farm insects for different purposes and in an economic way.